PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR IPAS SISWA DI KELAS V SD NEGERI 21 SINGKAWANG: Penelitian Kuantitatif - Atikah, Nuri; Safrihady; Suwanto, Insan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low learning outcomes of students in Natural and Social Sciences (IPAS) in grade V of SD Negeri 21 Singkawang, which have not yet reached the Learning Objective Achievement Criteria (KKTP). The objectives of this study are: 1) To test whether there is a significant effect of the implementation of the Problem-Based Learning (PBL) model on the learning outcomes of fifth-grade students at SDN 21 Singkawang in the subject of Natural and Social Sciences (IPAS). 2) To determine the extent of the effect of using the Problem-Based Learning (PBL) model on the learning outcomes of fifth-grade students at SDN 21 Singkawang in the subject of Natural and Social Sciences (IPAS). This study uses a quantitative approach with an experimental research design, specifically a Pre-Experimental Design of the One-Group Pretest-Posttest Design type. The research subjects were 29 fifth-grade students at SDN 21 Singkawang. Data were collected using a multiple-choice question technique consisting of 20 items. Data analysis included normality tests using Chi-Square and hypothesis tests to determine the effect, as well as Effect Size calculations to determine the magnitude of the effect. The results of the study indicate that: 1) there is a significant difference between the pre-test and post-test scores after the implementation of the PBL model. The One Sample T-Test shows a t-stat value of - 12.28, which is much greater than the critical t-value of 1.70, with a p-value of 1.4396 × 10⁻¹², which is less than 0.05. This means that the null hypothesis is rejected and the alternative hypothesis is accepted. 2) The calculation result of 0.64 indicates that the effect of the PBL model on IPAS learning outcomes is in the large category